Sensibilidade a antimicribianos de bacteroidales de microbiota intestinal de cães e o efeito de concentracöes subinibitórias de antimicrobianos na formação de biofilme in vitro - Silva, Janice Oliveira (2015)
The Bacteroides and Parabacteroides spp are involved in serious diseases like abscesses and bacteremia in humans and animals. These bacteria are characterized by antimicrobial resistance and B. fragilis is the main anaerobic bacteria isolated from the intestine which can form biofilm. The aim of this study was to isolate Bacteroides and Parabacteroides strains from dogs intestinal tract, to investigate the antimicrobial susceptibility and to evaluate the action of antimicrobials subinhibitory concentrations on biofilm formation. A total of 30 strains were evaluated in this study. The assays were performed in accordance with the Clinical and Laboratory Standards Institute (CLSI) guidelines and other established methods. Antimicrobial susceptibility was observed against penicillin, amoxicillin-clavulanic acid, cefoxitin, imipenem, clindamycin, ciprofloxacin, enrofloxacin, tetracycline, chloramphenicol and metronidazole. Fifteen B. fragilis strains were tested for biofilm formation and the stronger four biofilm producer strains were chosen to evaluate the effect of subinhibitory concentrations (1/2 and 1/4MIC) of six antimicrobials on biofilm formation. B. fragilis was the most frequently isolated anaerobic bacteria followed by P. distasonis and B. vulgatus. The isolates were uniformly susceptible to metronidazole, imipenem and chloramphenicol and were penicillin resistant. Tetracycline and clindamycin were active against 50% and 33% of the strains respectively. The biofilm production of all four strains was uniformly and significantly lower (P<0.05) after growth with ½ MIC and ¼ MIC of imipenem and metronidazole. The induction of biofilm formation was observed in two isolates at ½ MIC and ¼ MIC of enrofloxacin.